2017
DOI: 10.1038/s41598-017-17686-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocortisone administration was associated with improved survival in Japanese patients with cardiac arrest

Abstract: There are few reports on hydrocortisone administration after cardiac arrest, and those that have been published included few subjects. This study aimed to evaluate the effect of hydrocortisone administration on the outcomes of patients who experienced cardiac arrest. We investigated the survival discharge rates and the length of hospital stay from cardiac arrest to discharge, stratified by use of hydrocortisone, using a Japanese health-insurance claims dataset that covers approximately 2% of the Japanese popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 14 publications
1
46
0
Order By: Relevance
“…In another retrospective study conducted in Japan by Nimura et al with both IHCA and OHCA patient data, they also found an improvement in survival rate to hospital discharge and decrease in the length of hospital stay from cardiac arrest to discharge due to hydrocortisone administration during CPR 13 . Both of these studies were performed with a large number of subjects to ensure higher statistical power 11,13 . However, due to the retrospective nature of these studies, they have some limitations, such as: (a) the subjects could not be randomized, and (b) effect of different steroid dosage could not be measured appropriately.…”
Section: Review Articlementioning
confidence: 83%
See 1 more Smart Citation
“…In another retrospective study conducted in Japan by Nimura et al with both IHCA and OHCA patient data, they also found an improvement in survival rate to hospital discharge and decrease in the length of hospital stay from cardiac arrest to discharge due to hydrocortisone administration during CPR 13 . Both of these studies were performed with a large number of subjects to ensure higher statistical power 11,13 . However, due to the retrospective nature of these studies, they have some limitations, such as: (a) the subjects could not be randomized, and (b) effect of different steroid dosage could not be measured appropriately.…”
Section: Review Articlementioning
confidence: 83%
“…Due to potential benefits of steroid use, there has been a recent trend in the medical community across the globe to perform clinical research on the effects of administering steroids to patients in cardiac arrest during CPR 10,11,12,13 . Tsai et al conducted a retrospective cohort study with the data from the Taiwan National Health Insurance Research Database to determine the effect of steroids in OHCA outcomes 11 .…”
Section: Effect Of Steroid In Cardiac Arrestmentioning
confidence: 99%
“…The main characteristics of the included studies are shown in Table 1, and the outcome data from each included study are shown in Table 2. We included seven studies 7,8,[12][13][14][15][16] in our analysis. These studies were published between 2001 and 2019.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…Six studies 7,[12][13][14][15][16] examined the association between steroid use and ROSC. Among these six studies, four studies were RCTs and two were cohort studies.…”
Section: Primary Outcome: Roscmentioning
confidence: 99%
See 1 more Smart Citation